"I Wouldn't Stay Here": Economic Crisis and Youth Mobility in Ireland. (21st August 2012) - Cairns, David
Abstract In this paper, I explore an important aspect of Irish youth migration, in both Northern Ireland and the Republic of Ireland, namely the mobility intentions of tertiary‐educated youth during the recent economic crisis. Building on prior work that I completed in 2007, I conducted quantitative and qualitative research with a total of 400 university students in Dublin, Belfast and Cork during 2010. Analysis of the data reveals that the majority of these young people (62%) intend to leave Ireland in the future, moving predominantly to other English‐language speaking countries, with such plans being more prevalent in the Republic of Ireland (72%) compared to Northern Ireland (52%). Further quantitative analysis and a series of qualitative interviews help explain what has influenced the mobility decision‐making of these young people. The results emphasize the importance of factors such as parental occupational background and locality, as well as the role of family relationships in encouraging and discouraging mobility. The impact of the economic crisis is, however, less clear, with the mobility intentions of young people planning to migrate tending to be influenced more by personal than economic considerations.